Integrating a wood carving manufacturing facility with a cultural museum through a narrative architectural approach in Paete, Laguna. - Sinco, Avron John Henri S. (College of Architecture, University of the Philippines Diliman, 2025)
Deeply rooted in Paete’s identity and culture, the municipality’s wood carving industry continues to struggle against the issues of craft staging and their fragmented production process. As such, the study explores how architectural strategies can provide for the industry’s marketing, improvement, and advancement through the proposal of an integrated Paete Wood Carving Manufacturing Facility and Museum. The design is mainly based on the concepts of narrative architecture and architectural storytelling, highlighting the importance of architectural features in the unfolding of the wood carvers’ stories. These concepts were partnered with the provision of an artisan coworking space to encourage collaboration and foster product quality improvement and artisan skills development. A thematic analysis and simplified cultural mapping were utilized to extract pertinent themes, tones, and narratives from the interviews with the wood carvers, researchers, and government officials. These themes were used as the main basis for the construction and arrangement of architectural elements and spaces in the program. In addition to this, the town’s susceptibility to natural hazards (i.e. flooding and landslides) and the proliferation of Spanish-originated traditions and customs were also used as main considerations in the design. Overall, this research envisions a collaborative, immersive, culturally appropriate, and climate sensitive museum and manufacturing facility that will not only aid Paete’s wood carvers in sustaining their craft, but also in solidifying their identity as well.